Cardiac magnetic resonance in heart failure with preserved ejection fraction: myocyte, interstitium, microvascular, and metabolic abnormalities. (7th August 2020) - Quarta, Giovanni; Gori, Mauro; Iorio, Annamaria; D'Elia, Emilia; Moon, James C.; Iacovoni, Attilio; Burocchi, Simone; Schelbert, Erik B.; Brambilla, Paolo; Sironi, Sandro; Caravita, Sergio; Parati, Gianfranco; et al.
Abstract: Heart failure (HF) with preserved ejection fraction (HFpEF) is a chronic cardiac condition whose prevalence continues to rise, with high social and economic burden, but with no specific approved treatment. Patients diagnosed with HFpEF have a high prevalence of comorbidities and exhibit a high misdiagnosis rate. True HFpEF is likely to have multiple pathophysiological causes – with these causes being clinically ill‐defined due to limitations of current measurement techniques. Myocyte, interstitium, microvascular, and metabolic abnormalities have been regarded as key components of the pathophysiology and potential therapeutic targets. Cardiac magnetic resonance (CMR) has the capability to look deeper with a number of tissue characterization techniques which are closer to the underlying specific abnormalities and which could be linked to personalized medicine for HFpEF. This review aims to discuss the potential role of CMR to better define HFpEF phenotypes and to infer measurable therapeutic targets.